Analysis of Lycopene Content and Antioxidant Activity Test of Katokkon Chili Extract (Capsicum chinense Jacq) - Febryna V. Maddo; Siti Aminah; Afadil Afadil (Universitas Tadulako, 2021)
This study aimed to determine lycopene contents and the antioxidant activity of katokkon chili extract. The extraction process of katokkon chili used the maceration method with the mixture of n-hexane : acetone : ethanol (2:1:1). The concentrated extract of katokkon chili was obtained through the evaporator process at a temperature of 40 ˚C. The analysis process used a UV-Vis spectrophotometer in which the absorbance reading was at λ = 472 nm. The average content of lycopene in katokkon chili extract was 1.457 mg/100g. Testing the antioxidant activity of katokkon chili extract used the DPPH (2,2-diphenyl-1-picrylhydrazyl) method with positive control the vitamin C. The absorbance readings for the antioxidant activity test were at λ = 517 nm. The test results showed that the antioxidant power of katokkon and vitamin C extracts in reducing DPPH free radicals had a similar result which was equally strong. The IC50 value for chili katokkon extract was 13.84 mg/L, and the IC50 value for vitamin C was 5.78 mg/L, so it can be concluded that chili katokkon can be an alternative source of natural antioxidants to replace vitamin C.